Drinking goal choice and outcomes in a Web-based alcohol intervention: Results from VetChange. (March 2015) - Enggasser, Justin L.; Hermos, John A.; Rubin, Amy; Lachowicz, Mark; Rybin, Denis; Brief, Deborah J.; Roy, Monica; Helmuth, Eric; Rosenbloom, David; Keane, Terence M.
Abstract: Objectives: The objectives of the paper are to describe characteristics of participants who chose moderation and abstinence drinking goals, and to examine post-treatment drinking outcomes based on patterns of goal choice during a Web-based alcohol intervention for returning U.S. Veterans. Method: We conducted a descriptive secondary analysis of a subsample of 305 of 600 Veterans who participated in a clinical trial of VetChange, an 8-module, cognitive-behavioural intervention. Participants self-selected abstinence or moderation drinking goals, initially at Module 3, and weekly during subsequent modules. Alcohol use and alcohol-related problems were measured using the Alcohol Use Disorders Identification Test (AUDIT), Quick Drink Screen (QDS), and Short Inventory of Problems (SIP-2R). Results: Initial goal choices were 86.9% moderation and 13.1% abstinence. Approximately 20% of participants from each initial choice changed goals during the intervention; last goal choices were 68.6% moderation and 31.4% abstinence. Participants who initially chose moderation reported higher percent heavy drinking days at baseline; participants who initially chose abstinence were more likely to report recent substance abuse treatment and were older. Post-intervention levels of alcohol use and alcohol-related problems were significantly reduced in all goal-choice patterns (i.e., Moderation Only, Abstinence Only, Moderation to Abstinence, and Abstinence to Moderation; all measures p < 0.05 or less). Baseline drinking severity did not differentially relate to outcomes across goal-choice patterns. Conclusions: Participants in a Web-based alcohol intervention for returning U.S. Veterans demonstrated improvements in drinking regardless of whether they chose an abstinence or moderation drinking goal, and whether the goal was maintained or changed over the course of the intervention. Highlights: We provide a description of drinking goals and outcomes in a Web-based intervention. Participants in the Web intervention chose moderation goals most often. Both abstinence and moderation goals led to significant reductions in drinking. Drinking improved when a goal was either maintained or changed during intervention. Allowing for self-selection of drinking goals was associated with positive outcomes.